Socialization of Higher Education Major Selection Literacy for 12th Grade Students of SMKN 7 Palembang - Aravik, Havis; Marnisah, Luis; Tohir, Ahmad (Institut Riset dan Publikasi Indonesia, 2026)
Choosing a college major is an important academic decision that determines the direction of education, competency development, and career readiness of students after completing secondary education. However, in practice, many students still choose majors without adequate understanding of the study program, interests, talents, and academic prospects, potentially leading to wrong choices when entering college. This condition can have an impact on academic stress, low learning motivation, and unsuitable study directions. This community service activity aims to provide literacy in choosing college majors to grade XII students so they can make study choices more rationally and in accordance with their potential. The activity was carried out on January 15, 2026 at SMKN 7 Palembang in the Department of Mechanical Engineering and Motorcycle Engineering with 30 participants using an educational-participatory approach through lectures and interactive discussions. The lecture method was used to convey material regarding the importance of higher education, introduction to study programs, the relationship between interests and talents with major choices, and the risks of making mistakes in choosing a major. Furthermore, interactive discussions were held to deepen participants' understanding through direct questions and answers regarding major choices, college life, college entrance paths, and strategies for being a good student. The results of the activity showed that participants were highly enthusiastic, actively participated in discussions, and demonstrated an increased understanding of the importance of literacy in selecting a college major. Evaluation of the activity also indicated that students viewed the activity as highly beneficial in providing valuable resources for making informed and focused choices for further study.